Reductions in Perceived Injustice are Associated With Reductions in Disability and Depressive Symptoms After Total Knee Arthroplasty. Issue 5 (May 2018) - Yakobov, Esther; Scott, Whitney; Stanish, William D.; Tanzer, Michael; Dunbar, Michael; Richardson, Glen; Sullivan, Michael J.L.
Abstract : Introduction: Perceptions of injustice have been associated with problematic recovery outcomes in individuals with a wide range of debilitating pain conditions. It has been suggested that, in patients with chronic pain, perceptions of injustice might arise in response to experiences characterized by illness-related pain severity, depressive symptoms, and disability. If symptoms severity and disability are important contributors to perceived injustice (PI), it follows that interventions that yield reductions in symptom severity and disability should also contribute to reductions in perceptions of injustice. The present study examined the relative contributions of postsurgical reductions in pain severity, depressive symptoms, and disability to the prediction of reductions in perceptions of injustice. Methods: The study sample consisted of 110 individuals (69 women and 41 men) with osteoarthritis of the knee scheduled for total knee arthroplasty (TKA). Patients completed measures of perceived injustice, depressive symptoms, pain, and disability at their presurgical evaluation, and at 1-year follow-up. Results: The results revealed that reductions in depressive symptoms and disability, but not pain severity, were correlated with reductions in perceived injustice. Regression analyses revealed that reductions in disability and reductions in depressive symptoms contributed modest but significant unique variance to the prediction of postsurgical reductions in perceived injustice. Discussion: The present findings are consistent with current conceptualizations of injustice appraisals that propose a central role for symptom severity and disability as determinants of perceptions of injustice in patients with persistent pain. The results suggest that the inclusion of psychosocial interventions that target depressive symptoms and perceived injustice might augment the impact of rehabilitation programs made available for individuals recovering from TKA.